Cola para quem tem fome: um ensaio sobre as potencialidades e limitações da sociologia da fome - Rêgo, David Loiola (2009)
This work aims to present a systematic study of sociology developed by Josué de Castro. It is a theoretical work that aims to evidence the potentialities and limitations of the hunger analysis theoretical models of contemporary sociology. It was used concepts of Social Institution (Berguer and Bourdieu), Habitus-precário and Ralé (Jessé Sousa) as weapons to comprehend better the hunger phenomenon on the sociology field, to consequently generate dialogs between Castros writings and the contemporary sociology. It demonstrates how hunger reproduces more by pre reflexive behavior patterns in a way that the moral rules become invisible and allow the phenomenon to continue in an invisible way